INNOVATIVE PREREQUISITES FOR THE FORMATION OF THE COMPANY’S BRAND DEVELOPMENT STRATEGY - Титикало, Володимир С. (Journal of Strategic Economic Research, 2024)
The article examines modern challenges and threats faced by domestic enterprises, which are caused by military actions on the territory of Ukraine, a deep political crisis and the same crisis phenomena in the economy, the strengthening of the fight for the client, the oversaturation of the markets with services and goods and the decrease in the purchasing power of consumers Reasonably effective mechanisms of brand development to increase competitive advantages and recognition among other market players for positioning in leading positions. The policy of companies that resort to the formation and effective implementation of brand management in the general management system of the enterprise was investigated, the key problems in brand management of the studied agricultural company were diagnosed, and directions for improving the brand management of the studied enterprise were formed. It was determined that the management of brands at agricultural enterprises can strengthen the competitiveness of the latter by providing them with long-term competitive advantages and building close loyal relations with the consumer. Moreover, today the role of environmentalization of society, food security and the desire of people to consume high-quality natural food products is growing significantly, therefore the role of farmers as producers of strategically important products will increase, which means that it is necessary to distance yourself from competitors in the eyes of society, stand out, show your best strengths and skillfully hide the weak.